A Physical Activity Intervention Demonstration Project Among Employees of Universiti Putra Malaysia - Sin, Yong Wai (2005)
Physical activity is important for enhancing health and to reduce risk of various chronic diseases.Despite the well-known benefits of physical activity, lack of physical activity is now a global health hazard.Worldwide,more than 60% of adults do not engage in sufficient levels of physical activity to achieve health benefits (WHO, 2003a). In Malaysia, approximately 31% of adults do not exercise regularly (MOH, 1998).The study objective was to evaluate the effects of a six-week physical activity intervention at worksite on anthropometric measurements,percentage of body fat, physical activity levels,physical activity stages of change,walking energy expenditures and barriers to exercise.A total of 110 employees from six randomly selected faculties in Universiti Putra Malaysia were randomly allocated into control (3 faculties, n=55) and intervention groups (3 faculties, n=55). Over the six-week period, the intervention group received a multi-component intervention consisting of lecture-discussion sessions, group counselling sessions, exercise demonstrations, posters, weekly booklets and telephone reminders. The control group received weekly booklets only.Baseline and postintervention assessments were conducted by using the same questionnaires (interviewadministered format). Interviews,intervention activities and written information were conducted in Bahasa Melayu.At the end of the study, a significant positive change(p<0.05) was found for the percentage of body fat,physical activity level, physical activity stages of change,walking energy expenditure and three categories of barriers to exercise namely,lack of time, social influence and lack of willpower in the intervention group.A non-significant improvement in physical activity level,physical activity stages of change and barriers to exercise was observed for the control group.This finding may indicate that the written information (booklets) may have had some impact on promoting a physically active lifestyle or may also be due to external factors that were not controlled for.In conclusion,more than 60% of all the participants were engaged in little or no exercise at the beginning of the study. The recorded positive changes after the six weeks intervention provide evidence to support that a short-term intervention could help to increase the proportion of individuals meeting the recommendations of physical activity, adopt positive physical activity behaviour and decrease the number of barriers to exercise.Therefore, the implementation of physical activity interventions at worksites should be encouraged